ANALISA YURIDIS KEDUDUKAN PEMERINTAH DESA DALAM PENGGUNAAN DANA DESA MENURUT UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - Elita Tampubolon (Nommensen Journal of Legal Opinion, 2022)
State of Indonesia is a Unitary State, in the form of a Republic, where in all countries there is only one government, namely the Central Government, but a form of decentralization still needs to be carried out. Decentralization as the forerunner to the birth of regional autonomy which in the end also gave birth to village government as the smallest scope in implementing the autonomy system. This study aims to find out how the form of the position of the Village Government in Indonesian Constitutional Law in terms of organizing government activities on the use of village funds based on Law Number 6 of 2014 concerning Villages. The benefit of this research is to increase understanding of the form of the Village Government's position and its duties, authorities, rights and responsibilities based on the provisions of the Act. This writing uses the method in normative legal research, the author in his research collects secondary data related to the problems discussed then analyzed and stated descriptively. The division of power in the administration of government inIndonesia is horizontal and vertical. Horizontally, it is known as the division of legislative, executive and judicial powers, while the vertical division of power is the division of power between several levels of government. Village government is the administration of government affairs and the interests of the local community in the Government System of the Unitary State of the Republic of Indonesia. As the smallest level of government scope, it is carried out by the Village Government. The village government is the village head or what is called by another name assisted by village officials as an element of village administration. The Village Head is in charge ofadministering Village Government, implementing Village Development, developing Village community, and empowering Village communities. As the organizer of the Village Government, the Village Head is the holder of the highest authority in the Village Government system, while in the government system Indonesian, the Village Government is under the Regency/City government. In accordance with Law no. 6 of 2014, the implementation of Village Government is based on the principles of:  openness, proportionality, professionalism, accountability, effectiveness and efficiency,wisdom local, diversity and participation.